2020
DOI: 10.21203/rs.3.rs-93543/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation of CoIV=O intermediate at the Boundary of the “Oxo-wall” Induces Water Oxidation

Abstract: Development of economically viable artificial photosynthesis requires use of 3d metal-based catalysts. Water oxidation by [Co4O4]n+ cubane mimics water splitting by CaMn4O5 cluster in Nature but the exact mechanism of O-O bond formation is presently unknown. We demonstrate first in situ detection CoIV=O (~ 1.67 Å) moiety formed upon activation of [Co4O4Py4Ac4]0 (Py = pyridine and Ac = CH3COO−) towards O-O bond formation. Combined spectroscopic and DFT analyses show that the intermediate active in O-O bond form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Craig and coworkers considered seventeen molecular OER catalysts based on a variety of transition metals (Ru, Ni, Mn, Co, Cu, and Fe); ruthenium acts at the metal center in nine of these seventeen catalysts. They found that unmodified use of conventional scaling relations for heterogeneous systems did not accurately predict the catalytic activity of a set of homogenous catalysts; typical OER−scaling relations addressing the OER for heterogenous systems neglects the ET reaction from Ru IV [72][73][74]. As such, that our work focuses more on high−valent redox and WNA reactions is appropriate given our exclusive focus on the Ru metal center.…”
Section: Discussionmentioning
confidence: 99%
“…Craig and coworkers considered seventeen molecular OER catalysts based on a variety of transition metals (Ru, Ni, Mn, Co, Cu, and Fe); ruthenium acts at the metal center in nine of these seventeen catalysts. They found that unmodified use of conventional scaling relations for heterogeneous systems did not accurately predict the catalytic activity of a set of homogenous catalysts; typical OER−scaling relations addressing the OER for heterogenous systems neglects the ET reaction from Ru IV [72][73][74]. As such, that our work focuses more on high−valent redox and WNA reactions is appropriate given our exclusive focus on the Ru metal center.…”
Section: Discussionmentioning
confidence: 99%